Evaluation of Capacity and Function of Cold Chain Facilities at Fishing Port of Integrated Marine Fisheries Center (PP SKPT) Daeo, Morotai Island Regency - Rais, Djunaidi; Hi. Iksan, Kusdi; Achmad, M. Janib (Agrikan Jurnal Agribisnis Perikanan, 2024)
The aim of this research is to evaluate the capacity, function and level of utilization of cold chain facilities (Ice Factory, ABF and Cold Storage), and determine the level of satisfaction with cold chain facility services. The research was carried out at the Fisheries Port of Integrated Marine Fisheries Center (PP SKPT) Daeo, Morotai Island Regency. The research was conducted from April – May 2024. This research uses a case study method. Facilites of cold chain at PP SKPT Daeo consists of 1 unit of Ice Factory with installed capacity of 10 tons, production capacity of 10 tons/day, actual demand 28.15 tons/day, utilization rate (281,502%); 1 unit ABF with installed capacity 6 tons, production capacity 4.2 tons/day, actual need 12 tons/day, utilization rate (285.71%), exceeds optimal needs; 1 unit Cold storage with installed capacity 150 tons, production capacity 105 tons/day, actual demand 126 tons/day, utilization rate (120%); Stakeholder perceptions regarding satisfaction with cold chain facility services at PP SKPT Daeo: Fishermen, suppliers/fish collectors expressed dissatisfaction, while the Fish Processing Unit stated they were very satisfied.